Between Mountains and Modern Medicine: Adaptability in Anesthesia Training in Switzerland: Anesthesia Training in Switzerland - Estilita, Joana Berger (Journal of the Portuguese Society of Anesthesiology, 2024)
Switzerland's healthcare system is globally recognised for its access to care, supported by a robust network of hospitals and private healthcare providers. The Swiss anaesthesia workforce consists of approximately 2700 physicians, including specialists and trainees, with a notable presence of international medical graduates, predominantly from Germany. The country also relies heavily on nurse anaesthetists, who undergo extensive training to support anaesthesia procedures under physician supervision. Becoming an anaesthesia trainee in Switzerland requires a medical degree compliant with EU or EFTA standards and proficiency in one of the three official languages (German, French, or Italian). The residency program is regionally divided, with different structures in the German-speaking and French-Italian regions. The Swiss anaesthesia residency spans five years and emphasises a competency-based curriculum that includes mandatory anesthesiology and intensive care rotations. Training facilities are categorised into four levels (A1, A2, B, C) based on their training quality and scope. Residents undergo rigorous assessment through continuous evaluations, practical and written exams, and contributions to medical literature. The Swiss Institute for Post-Graduate and Continuous Medical Education (SIWF/FMH) oversees the certification process. Challenges in the training system include managing workload and stress, with ongoing campaigns to reduce clinical hours from 50 to 42 per week and ensure teaching time. Long waiting times for rotations in A Level clinics and the need to match the growing elderly population with sufficient trained anesthesiologists also present significant challenges. Addressing these issues through curriculum development, workload management, and increased training opportunities is crucial for maintaining the high standards of anesthesiology in Switzerland and meeting future healthcare demands.